Adiponectin and leptin levels in migraineurs: Results from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). (13th October 2020) - Goulart, Alessandra C; de Almeida-Pititto, Bianca; Lotufo, Paulo A; Santos, Itamar S; Ferreira, Sandra RG; Benseñor, Isabela M
Background: Relationships of adipokines (ADP) with migraine are not well-established. We examined the relationship of adiponectin and leptin with migraine by aura symptoms. Methods: In a baseline cross-sectional data of Brazilian Longitudinal Study of Adult Health (ELSA-Brasil), associations of ADP levels and migraine were assessed in a sample of 257 nondiabetic subjects, free from cardiovascular disease. Associations of ADP tertiles (dependent variable) and migraine status were tested using logistic regression models. Categories of migraine were created as follows: no headache (reference), migraine with aura (MA), and migraine without aura (MO) in all sample and by sex. Odds ratio (OR) with respective 95% confidence interval (CI) adjusted for age, sex, body mass index, and metabolic syndrome. Results: Among participants (46 years ± SD: 4.8), 47.5% were women and 36.2% had migraine (16.7% MA). Median values of leptin (ng/mL) increased gradually across subgroup: no headache: 9.5 (interquartile range (IQR): 5.5–15.7) versus MO: 17.0 (IQR: 10.9–34.2) versus MA: 20.9 (IQR: 11.7–29.3), overall p value <0.0001, but not for adiponectin levels. After full adjustment, the third of leptin was positively associated with MA (OR 2.89 (1.00–8.4)) and the second of adiponectin was associated with MO (OR 2.76; 95% CI: 1.09–6.96, p = 0.03). Positive associations with MA, second (OR 3.81; 95% CI: 1.07–13.59; p = 0.04) and third tertile of leptin (6.54; 95% CI: 1.74–24.57, p = 0.005), were also observed in women, but not in men. Conclusions: Positive associations between ADP and migraine, particularly between MA and leptin levels in women, raise the possibility of adipocytokines and play a role in migraine pathophysiology.